The Change in HbA1c Associated with Initial Adherence and Subsequent Change in Adherence among Diabetes Patients Newly Initiating Metformin Therapy - Gregory A. Nichols; A. Gabriela Rosales; Teresa M. Kimes; Kaan Tunceli; Karen Kurtyka; Panagiotis Mavros (Journal of Diabetes Research)
Introduction. Whether changes in adherence are associated with changes in HbA1c is assumed but not known. Methods. We conducted a observational study of 2,844 type 2 diabetes patients who initiated metformin as their first antihyperglycemic drug. Using HbA1c measures before, 6–12 months after, and up to 3 years after metformin initiation, we analyzed HbA1c change as a function of initial adherence and change in adherence. Results. Compared with no adherence, initial adherence of 50–79% was associated with an adjusted reduction in HbA1c of 0.45% while adherence ≥80% was associated with HbA1c reduction of 0.73%. Change from some initial adherence (1–79%) to total nonadherence was associated with 0.25% increase in HbA1c. Change from some to full adherence was associated with an HbA1c decrease of 0.15%. Those associations were accentuated among patients not in glycemic control: change from some to no adherence was associated with an HbA1c increase of 0.63% and change from some to full adherence was associated with an HbA1c decrease of 0.40%. Conclusions. Initial adherence to newly prescribed metformin therapy produces substantial HbA1c reduction. Among those with modest adherence but suboptimal glycemic control, the difference between moving to full adherence versus nonadherence results in lower HbA1c of one percentage point.